Iraq A Lost War - El-Shibiny, M.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2010)
Iraq: A Lost War deals with the impact of September 11th on the occupation of Iraq and the U.S. declaration of war on international terrorism. It investigates whether war in Iraq was morally justified and whether coalition forces capturing and hanging its president were morally and legally acceptable internationally.
Keywords: Middle East—Politics and government; International relations; Political science; Terrorism; Political violence; Middle Eastern Politics; International Relations; Political Science; Terrorism and Political Violence